2020
DOI: 10.3390/su12166663
|View full text |Cite
|
Sign up to set email alerts
|

Use of Recycled Aggregates Made from Construction and Demolition Waste in Sustainable Road Base Layers

Abstract: Research has been carried out on recycled aggregates from the exclusive crushing of structural concrete waste (CDWRCon) and mixed ceramic materials (CDWRCer) in selective demolitions. This study analyses the use of these recycled aggregates as wet mix macadam (GARCon, GARCer) and in cement soil (CSRCon, CSRCer). The materials comply with the requirements of a road base; although, due to the low values of resistance to fragmentation, these materials are adequate for use in sensitive road systems and other place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…This fact notwithstanding, large quantities of BOF slag can meet the needs of aggregates for road construction. The use of waste and by-products is one of the most promising techniques for sustainable roads, as it provides a double benefit [16]. On the one hand, it reduces the extraction and production of raw materials, reducing the consumption of water, electricity and diesel, as well as the generation of other diffuse emissions such as noise and dust.…”
Section: Introductionmentioning
confidence: 99%
“…This fact notwithstanding, large quantities of BOF slag can meet the needs of aggregates for road construction. The use of waste and by-products is one of the most promising techniques for sustainable roads, as it provides a double benefit [16]. On the one hand, it reduces the extraction and production of raw materials, reducing the consumption of water, electricity and diesel, as well as the generation of other diffuse emissions such as noise and dust.…”
Section: Introductionmentioning
confidence: 99%
“…The development of concrete or pavement by utilizing waste has been carried out by several researchers, especially recycled material waste. Some researchers use the concrete waste from building demolition as a substitute for coarse aggregate as a road pavement layer [6][7][8]. The results of this study indicate that the recycled aggregate can be used as a coarse base or sub-base on road pavements that are passed by light to medium volume vehicles such as residential roads or parking lots.…”
Section: Figure 1 Unused Construction Demolition Wastementioning
confidence: 84%
“…At the same time, to accelerate the sustainable development of resources, there is also a current research hotspot surrounding the crushing and screening of the waste concrete blocks produced by building demolition into recycled aggregates, which are then applied in road engineering [ 18 , 19 , 20 , 21 ]. Teijon et al [ 22 ] and Garach et al [ 23 ] first confirmed the feasibility of recycled aggregate as a road base. Then, Chiranjeevi et al [ 24 ] and Tefa et al [ 25 ] tested the road performance of a cement-stabilized recycled aggregate mixture and found that it had good compressive strength and could be used for low-grade roads.…”
Section: Introductionmentioning
confidence: 99%